Bulgarian Contribution to the Open Science Services in NI4OS-Europe - Karaivanova, Aneta; Atanassov, Emanouil; Gurov, Todor; Stanchev, Peter; Simeonov, Georgi (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2022)
The paper gives an overview on the Bulgarian participation in the einfrastructure part of the NI4OS-Europe project, funded by EC through H2020 program. NI4OS-Europe team has identified a set of necessary services and the corresponding policies that resources have to produce and publish, clearly stating to the users the ways these resources could be used, as well as the actions that are not allowed. By offering service providers a clear procedure for onboarding, NI4OS-Europe project partners are able to on-board more services with pan-European significance. Here we briefly present some of the services developed by the Bulgarian team.